Towards a revision of the South American genus Praocis Eschscholtz (Coleoptera, Tenebrionidae), with estimation of the diversity of each subgenus - Flores, Gustavo Ernesto (2014)
A review of the subgenera of the South American genus Praocis Eschscholtz (Pimeliinae: Praociini) is presented. Praocis comprises 77 species and 8 subspecies arranged in nine subgenera distributed in arid lands from Central Peru and Bolivia to the Southern part of Patagonia in Chile and Argentina. For each subgenus of Praocis: Praocis Eschscholtz, Mesopraocis Flores & Pizarro-Araya, subgen. n., Anthrasomus Guérin-Méneville, Filotarsus Gay & Solier, Postpraocis Flores & Pizarro-Araya, subgen. n., Hemipraocis Flores & Pizarro-Araya, subgen. n., Orthogonoderes Gay & Solier, Praonoda Flores & Pizarro-Araya, subgen. n., and Praocida Flores & Pizarro-Araya, subgen. n., we present a diagnosis using new and constant characters of adult morphology such as clypeal configuration, length and proportion of antennomeres 9, 10 and 11, arrangement of apical tomentose sensory patches on antennomeres 10 and 11, anterior margin of prosternum, lateral margin of elytron, ventral surface of profemora, and shape of protibiae. An identification key for the nine subgenera of Praocis is presented. Type species are designated for the five new subgenera; for Mesopraocis: Praocis calderana Kulzer, for Postpraocis: Praocis pentachorda Burmeister, for Hemipraocis: Praocis sellata Berg, for Praonoda: Praocis bicarinata Burmeister, for Praocida: Praocis zischkai Kulzer, and for the previously described subgenus Orthogonoderes: Praocis subreticulata Gay & Solier. The current number of species and the estimated number of species to be described are presented. The distribution ranges of the subgenera, including new records from collections and recent expeditions, are given. Habitat preferences and a discussion of the biogeography of the genus are also presented.